Airway Exosomes Released During Influenza Virus Infection Serve as a Key Component of the Antiviral Innate Immune Response - Bedford, James G.; Infusini, Giuseppe; Dagley, Laura F.; Villalon-Letelier, Fernando; Zheng, Ming Z. M.; Bennett-Wood, Vicki; Reading, Patrick C.; Wakim, Linda M. (Frontiers in Immunology, 2020)
Exosomes are extracellular vesicles secreted by cells that have an important biological function in intercellular communication by transferring biologically active proteins, lipids, and RNAs to neighbouring or distant cells. While a role for exosomes in antimicrobial defence has recently emerged, currently very little is known regarding the nature and functional relevance of exosomes generated in vivo, particularly during an active viral infection. Here, we characterised exosomes released into the airways during influenza virus infection. We show that these vesicles dynamically change in protein composition over the course of infection, increasing expression of host proteins with known anti-influenza activity, and viral proteins with the potential to trigger host immune responses. We show that exosomes released into the airways during influenza virus infection trigger pulmonary inflammation and carry viral antigen that can be utilized by antigen presenting cells to drive the induction of a cellular immune response. Moreover, we show that attachment factors for influenza virus, namely α2,3 and α2,6-linked sialic acids, are present on the surface of airway exosomes and these vesicles have the ability to neutralize influenza virus, thereby preventing the virus from binding and entering target cells. These data reveal a novel role for airway exosomes in the antiviral innate immune defence against influenza virus infection.